JS01.3.A Oncogenic chaperoning of Hsp90 in glioma with FGFR3-TACC3. (9th September 2021) - Li, T; Mehraein-Ghomi, F; Forbes, M; Namjoshi, S; Ballard, E; Song, Q; Chou, P; Wang, X; Yang, X; Zhang, W
Abstract: BACKGROUND: Fusion genes are chromosomal aberrations in malignancies that can be used as prognostic markers as well as therapeutic targets. The FGFR3-TACC3 ( F3-T3 ) was initially discovered as an oncogenic molecule in glioblastoma and bladder cancer and subsequently found in many other cancer types. Based on clinical evidence, F3-T3 was found in glioblastoma patients before and after TMZ and radiotherapy treatment, suggesting that targeting F3-T3 is a valid strategy for glioblastoma treatment. MATERIAL AND METHODS: We profiled the proteins that interacted with F3-T3 fusion protein in U-251 MG cells with F3-T3 through 2-D liquid chromatography-tandem mass spectrometry. To validate the result of proteomic analysis, we performed reverse immunoprecipitation by pulling down Hsp90 or Cdc37 in U-251 MG cells stably expressing F3-T3. To inhibit the association between F3-T3 and the Hsp90-Cdc37 complex, we treated U-251 MG and LN-229 cells stably expressing F3-T3 with Hsp90 inhibitors or siRNA of Cdc37. We applied the CCK8 assay to evaluate the sensitivity of glioblastoma cells stably expressing F3-T3, wild-type FGFR3, kinase-dead F3-T3 (K508R), and empty vectors to TMZ. Immunoblot and immunofluorescence staining were used to detect DNA damage marker pH2AX. The drug combination effect index was analyzed using software CalcuSyn. U-251 MG cells stably expressing F3-T3 infected with luciferase virus were intracranially injected in nude mice. The experimental group was administered with temozolomide (5mg/kg/day) by oral gavage, Hsp90 inhibitor Onalespib (30mg/kg/day) by tail vein injection or the combination of the two for indicated days. RESULTS: We identified the proteins that showed increased binding ratios to F3-T3 over full-length FGFR3, the molecular chaperone proteins encoded by the genes HSP90AB1, HSP90AA1, and CDC37 emerged as 5th, 6th, and 7th on the top ten list, showing an approximately 4-fold increase in normalized spectral counts. Using Hsp90 inhibitors or Cdc37 siRNA disrupted the formation of the F3-T3/Hsp90/Cdc37 complex. Disruption of Hsp90-Cdc37 chaperoning caused a ubiquitination-mediated degradation of the glycosylated form of F3-T3 and abrogated the maturation of nascent F3-T3, resulting in suppression of F3-T3 signaling pathways. Additionally, our results provide evidence that the F3-T3 signaling pathway confers drug resistance to TMZ induced DNA damage. However, the resistance of TMZ was disrupted in glioblastoma cells harboring kinase-dead F3-T3 (K508R). We also demonstrated Hsp90 inhibitor significantly sensitized glioblastoma cells harboring the F3-T3 fusion gene to TMZ treatment and improved survival of xenograft model bearing F3-T3 tumor in vivo. CONCLUSION: F3-T3 is a strong Hsp90 client that shows strong addiction to the Hsp90-Cdc37 chaperone system. Combination therapy with Hsp90 inhibitor overcomes the TMZ resistance conferred by F3-T3.